Investigation on the static fatigue mechanism and effect of specimen thickness on the static fatigue lifetime in WC–Co cemented carbides - Ding Chen; Liang Yao; Zhenhua Chen; Huiping Wang; Wen Peng (Сверхтвердые материалы, 2018)
The static fatigue mechanism and effect of specimen thickness on static fatigue lifetime for four WC–Co cemented carbides were studied with different binder contents and carbide grain sizes. Static fatigue tests under three-point bend loading were conducted on different sized specimens. The fracture surfaces of rupture specimens were examined by scanning electron microscopy to investigate the static fatigue micromechanisms.